Pelatihan Penyusunan Rencana Usaha (Business Plan) bagi UMKM Pemula di Kecamatan Amanuban Barat - Sauw, Heni Matelda; Bire, Amram Rohi; Sartien, Margaretha; Sinaga, Mentari; Maria, Maria (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting both national and local economic growth, including in Amanuban Barat District. However, many beginner MSMEs face challenges in developing their businesses due to a lack of understanding and skills in preparing a business plan. Without a well-structured plan, MSME actors find it difficult to manage risks, seize market opportunities, and access formal funding sources. The main problems faced by MSMEs in this area include a limited understanding of the importance of a business plan, insufficient technical skills in business planning, lack of access to mentoring and training, difficulties in obtaining business capital due to the absence of proper business documents, and low awareness of market and financial analysis. This community service program aimed to enhance MSME capacity through training on the importance of business planning and a technical workshop on simple business plan preparation. The training methods included lectures, interactive discussions, and hands-on business plan practice. The results showed a significant improvement in participants’ understanding of business planning, their ability to design a business plan, and their awareness of building networks and business collaboration. This activity has provided tangible benefits by helping MSMEs expand access to formal funding and optimize their business potential. Therefore, this program contributes to strengthening and sustaining local economic growth in Amanuban Barat District